"A Great Idea, Just Not Near Me!" Understanding Public Attitudes About Renewable Energy Facilities. Issue 12 (1st December 2016) - Larson, Eric C.; Krannich, Richard S.
ABSTRACT: Generally, the growth of renewable energy sources is supported by the American public. However, gaining acceptance of large-scale renewable energy projects from local residents is often difficult. Like many other states in the United States, Utah has several proposed, under construction, and operational renewable energy facilities and potential for significant renewable energy growth. However, several energy projects have been met with considerable local opposition. This study was undertaken to better understand Utah residents' attitudes toward wind and solar energy, and the variation in willingness to have utility-scale wind or solar facilities built in close proximity to their place of residence, using data collected through a statewide survey. Bivariate correlation and multiple regression analyses were used to explore relationships involving two dependent variables—general renewable energy attitudes, and respondents' willingness to have utility-scale wind or solar facilities built within close proximity to their place of residence. Possible implications of these findings are advanced.